Pengaruh Social Comparison Terhadap Fear of Missing Out Pada Mahasiswa di Universitas Negeri Padang - ALMAYNIWATI; Rizal Kurniawan (CAUSALITA : Journal of Psychology, 2024)
This research aims to determine the effect of social comparison on the fear of missing out among students at Padang State University. This research uses quantitative methods with a correlational quantitative design. The data collection technique uses cluster sampling. The data collection technique uses a questionnaire with a Likert scale model which is distributed with the help of the Google Form feature. The sample for this research was 188 respondents. The research instrument used Kurniawan & Utami's (2022) fear of missing out scale which was adapted from (Sette et al., 2020), as well as a social comparison scale based on aspects of Buunk et al., (2003). The results of the research used simple linear regression analysis and the results showed that social comparison had a positive and significant effect on fear of missing out in students at Padang State University.